Standard of care for HIV infected individuals/aids patients in Slovenia - Tomažič, Janez (Acta dermatovenerologica Alpina, Pannonica et Adriatica, 2003)
The routine screening protocol for Slovenian patients with established HIV infection is presented. Complete blood count is especially important in patients with HIV infection since anemia, leucopenia, lymphopenia and thrombocytopenia are found in 30% to 40% of patients. Serum chemistry panel iscommonly advocated in the initial evaluation of HIV infection due to high rates of hepatitis, multisystem diseases and multiple drugs that are potentially toxic. CD4 cell count is a standard test to stage the disease, to predict clinical progression and to make therapeutic decisions regarding antiviral treatment and prophylaxis for opportunistic pathogens. Quantitative plasma HIV RNA is useful for diagnosing acute HIV infection, for predicting progression in chronically infected patients and for therapeutic decisions andmonitoring. Genotypic resistance testing is indicated for chronically infected patients receiving antiretroviral drugs with treatment failure. Serological tests for hepatitis viruses, toxoplasmosis and cytomegalovirus infection, purified protein derivative (PPD) skin test, the venereal disease research laboratory (VDRL) test, Treponema pallidum hemagglutination (TPHA) test, Papanicolaou (PAP) smear test, fasting glucose and lipid profile are also performed. Chest x-ray is indicated for symptoms and signs suggesting pulmonary disease or newly detected positive PPD. When to start antiretroviraltherapy remains controversial. Though treatment is individualized, there are a lot of problems with compliance, adherence, tolerance, side effects, patient's quality of life and resistance of the virus.
Keywords: CD4 limfociti, štetje; Cd4 Lymphocyte Count; Citomegalovirus; Cytomegalovirus; Diagnosis; Drug Therapy; Hepatitis B Core Antigens; Hepatitis B, sredica, antigeni; Hiv Infections; HIV infekcije; Papillomavirus, Human; Papilomavirus človeški; RNA virusna; Rna, Viral; Sifilis; Syphilis; Toxoplasma; Tuberculin Test; Tuberkulinski test